Asuhan Kebidanan Komprehensif pada Ny. T Umur 31 Tahun dengan Risiko Tinggi Jarak Kehamilan Kurang dari 2 Tahun di Puskesmas Bumiayu Tahun 2024 - Endang Aguskristiana; Maryam Maryam; Khunelis Khunelis (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
High-risk pregnancy is a pregnancy with a number of risk factors that can cause more serious risks or complications and disrupt the pregnancy process until the postpartum period which endangers the life of the mother and fetus, and occurs due to several factors including pregnancies that are too close together, pregnancies with a mother's age that is too young or old, or pregnancies with too frequent births. Too close pregnancy spacing is a pregnancy gap of <24 months (2 years) between the current pregnancy and the previous pregnancy. Based on the midwifery management method described by VARNEY and SOAP, this study aims to offer complete midwifery care services to Mrs. T, from pregnancy to the use of contraceptives, through a qualitative descriptive method with a case study approach. Research findings from the comprehensive midwifery care assessment that has been provided to Mrs. T aged 31 years, in pregnancy found problems spacing of less than 2 years. Mrs. T gave birth spontaneously at Siti Asiyah Bumiayu Hospital with severe preeclampsia. At By. Mrs. T visits I, II, III no problems were found. Mrs. T's postpartum. From 6 hours postpartum to 42 days postpartum, problems were found at the second visit, including hypertension and lower extremity oedema. Proper care from midwives during pregnancy, childbirth, newborn care, postpartum care, and family planning is crucial for the health of both mother and baby.